Magnetic Moments of 70-Plet Baryons in Quark Model and QCD Sum Rules - T. M. Aliev; V. S. Zamiralov (Advances in High Energy Physics)
Magnetic moments of the positive parity 70-plet baryons are estimated in the framework of the nonrelativistic quark model and QCD sum rules method. It is found that the magnetic moments of the 70-plet baryons can be expressed in terms of the F and D couplings and exhibit unitary symmetry. The QCD sum rules for the magnetic moments of the 70-plet octet baryons are formulated. A comparison of our results on magnetic moments of 56-plet and 70-plet baryons predicted from QCD sum rules is presented.